Organoleptic Test of Chocolate Chips Cookies Made from Moringa Leaf Flour (Moringa Oleifera) - Parwitha, I Made Indra Maka; Winata, Gede Adi Sistha (PT FORMOSA CENDEKIA GLOBAL, 2024)
Moringa (Moringa Oleifera) is one type of plant that is very rich in nutrients, especially in its leaves. Moringa leaves have not been widely utilized due to the lack of public understanding to process them and the utilization of moringa leaves as processed food products has not been optimal. In this study, moringa leaves will be utilized as flour which will be used as the basic ingredient in making chocolate chips cookies. The purpose of this study was to determine the quality of chocolate chips cookies that use moringa leaf flour as the basic ingredient, using the organoleptic test research method. The methods used to support data collection are experiments, documentation, organoleptic tests, panelists, questionnaires and Likert scales. The data analysis technique used is descriptive qualitative. The research data in this organoleptic test, which was analyzed using a Likert scale, showed that research on chocolate chips cookies made from moringa leaf flour obtained an average score of 93% with very good interpretation criteria.